Pengaruh Norma Dan Faktor Sosio-Ekonomi Terhadap Tax Morale Dengan Tingkat Pendidikan Sebagai Variabel Pemoderasi - Ega Okli Roseptia; Primandita Fitriandi (JEMAP, 2023)
The puspose of this study is to analyze the impact of personal and social norms on tax morale with educational level as moderating variable. This study uses 150 taxpayers in Jabodetabek as respondents. This quantitative research is using the Partial Least Square-Structural Equation Modelling (PLS-SEM) method to process the data and SmartPLS software. The results of this study indicate that social norm (patriotism) has a positive and significant effect on tax morale, personal norm (religiosity) has a positive effect on tax morale too but insignificant. On the other hand, all socio-economic variables in this research show no significant effect on tax morale. Educational level, as moderating variable, also shows no significant effect and categorized as homologiser moderation. Based on these conclusions, one thing that can be taken into consideration by DJP is to ask religious leaders for help to socialize tax regulations to improve the tax compliance.